2007
DOI: 10.1007/s00128-007-9294-4
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer Industry Effluent Induced Biochemical Changes in Fresh water Teleost, Channa striatus (Bloch)

Abstract: The industrial activities pose threat to the life of aquatic organisms in many ways. This research communication presents an account of the impact of fertilizer industry effluent upon the levels of protein and the activity of lactate dehydrogenase (EC 1.1.1.28, LDH), a terminal key enzyme in glycolytic pathway, in different organs of a fresh water teleost fish, Channa striatus (Bloch). The fish exposed to different sublethal concentrations of fertilizer industry effluent (3.5, 4.7 and 7.0% v/v) equivalent to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 28 publications
4
22
0
Order By: Relevance
“…Similar type of decrease in the level of protein, lipid and glycogen were reported by Mcleay and Brown (1974), Yadav et al (2007), Sakr and Jamal Al lail (2005) and D'cruz, and Miramda (2006). The gradual accumulation of toxicants present in industrial effluent has shown drastic reduction in the protein, lipid and glycogen contents progressively in the fish tissues (Rogar, 1980).…”
Section: Discussionsupporting
confidence: 82%
“…Similar type of decrease in the level of protein, lipid and glycogen were reported by Mcleay and Brown (1974), Yadav et al (2007), Sakr and Jamal Al lail (2005) and D'cruz, and Miramda (2006). The gradual accumulation of toxicants present in industrial effluent has shown drastic reduction in the protein, lipid and glycogen contents progressively in the fish tissues (Rogar, 1980).…”
Section: Discussionsupporting
confidence: 82%
“…The test medium (water) properties were also regularly analyzed. The water temperature was maintained at 18 ± 0.5°C and water quality was monitored daily for pH (6.9 ± 0.1), electric conductivity (281 ± 3.5 lMho/ cm), total alkalinity (48.0 ± 0.7 mg/l), hardness (140.61 ± 4.3 mg/l), dissolved oxygen (7.4 ± 0.2 mg/l), and also for certain ions such as Na, K, Zn, Cr, Cl -and SO 4 2- (Yadav et al 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Such industrial activities pose serious threat to the life of aquatic organisms in many ways. The fertilizer industry effluent consists of certain toxic components such as ammonia and heavy metals (Zn and Cr) which might be responsible for causing metabolic impairment in the aquatic organisms which could even lead to their death (Ekweozor et al 2001;Bobmanuel et al 2006;Gaitonde et al 2006;Sarkar et al 2006;Yadav et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As the toxicity of the medium increases, the protein content in the tissues of hydrobionts decreases [57][58][59][60]. The protein content reflects the physiological state as a reaction to changes in the conditions of existence [61]. The dynamics of protein content in the body depends essentially on the environmental conditions of existence.…”
Section: Volume 70 the Effects Of Water Pollution On The Environmentmentioning
confidence: 99%